Pengaruh Kemampuan Berbahasa Arab Mahasiswa Fakultas Dakwah Unisba Angkatan 2017 terhadap Daya Hafalan Al-Qur’an - Muhammad Abdul Aziz Ibrohim (UNISBA Press, 2022)
Abstract. Both vocally and in writing, language is a communication tool for expressing ideas or emotions. The Koran, the Muslim language's sacred book, is written in Arabic. According to some, studying Arabic is something that is highly challenging and tough, thus they are still not interested in doing it. Students from the Islamic University of Bandung's 2017 graduating class of the Da'wah Faculty participated in this study. This study intends to ascertain the impact of students' Arabic language proficiency on Qur'an memorization in the Da'wah faculty at Unisba's 2017 graduating class. Therefore, it is anticipated that this research will have positive effects on students increasing their drive to memorize and master the Qur'an and that it will have positive effects for lecturers by making it easier to motivate students to learn the Qur'an. Researchers will hopefully reveal advantages of using and putting Arabic memorization to good use. Data were collected using interviews, questionnaires, observations, and archives. Validity tests, reliability tests, normality tests, testing for correlation coefficient analysis, regression analysis, and tests for hypotheses were used to analyze the data. The number of Arabic language proficiency and memorization surveys is at intervals of 1331.5, according to the processed data. According to the study's findings, students from the 2017 Unisba da'wah faculty's language in Arabic had a